Preferences on Vital and Nonvital Tooth Bleaching: A Survey Among Dentists from a City of Southern Brazil - Demarco,Flávio Fernando (2013)
This study evaluated the preferences of general dentists regarding vital and nonvital tooth bleaching therapies and investigated whether the time of clinical practice and post-graduate training influence these options. A cross-sectional study was conducted using a questionnaire with closed questions applied to dentists (n=276) of a mid-sized city of the southern Brazil (Pelotas, RS). Information was collected regarding sociodemographic variables, level of specialization and time since graduation. In addition, options regarding bleaching therapies including the first choice of material, technique and clinical practice for vital and nonvital tooth bleaching therapies were included. Data were submitted to descriptive analysis and the associations were evaluated using chi-square and Fisher exact tests (α=0.05). The response rate was 68% (n=187). At-home bleaching therapy was broadly preferred (78.1%) over in-office (21.9%) bleaching. For at-home bleaching, most dentists answered to use 10% carbamide peroxide (CP) (40.2%) and >30% hydrogen peroxide (HP) (31.7%) for nonvital therapies. The majority of dentists with post-graduation training preferred at-home bleaching techniques (p=0.003). At-home bleaching therapy was also more indicated by younger dentists. No association was found between the choice for nonvital bleaching therapies and time since graduation (p=0.532) or continuous education (p=0.083). In conclusion, at-home bleaching was preferred over in-office therapies; 10% CP and >30% HP were chosen as first option agents to treat discolored vital and nonvital teeth, respectively. The time in clinical practice and the level of specialization affected dentists' choices only for vital tooth bleaching treatment.